Using CMM-I-SE/SW continous model in the process area : Solsis case study (project planning) - Wan Ya Wan Hussin, author; Othman Yusop, supervisor; Fakulti Sains Komputer dan Sistem Maklumat (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2004)
Thesis (Sarjana Sains Komputer (Real Time Software Engineering)) - Universiti Teknologi Malaysia, 2004